Strategi Pengembangan UMKM Pasca COVID-19 - Tri Rumayanto; Siti Nurjannah Sanusi; Sihar Sihombing (Departement of Mathematics Education, 2022)
It is hoped that the economic recovery after the Covid-19 pandemic will soon see results through the revival of Micro, Small and Medium Enterprises (MSMEs). The government continues to provide support and ease in funding issues for MSMEs, besides that it is also hoped that the government through the Ministry of Cooperatives and MSMEs needs to provide support for strengthening MSME business development strategies including; strategic localization in the form of special areas for MSME centers, support for promotional activities, suggestions and instructions for choosing the right product, competitive pricing policies, as well as proven product quality, and equally important is human credibility. This strategy must be carried out in an effort to advance the nation's and state's economy.